Artificial intelligence support for knowledge management in construction - Mohamed, Sarajul Fikri; Zaibon, Syamsul Bahrin (2004)
The deployment of Artificial Intelligence (AI) tools and techniques to various problem domains in organisation has been steady since their introduction.On the other hand, knowledge management is an innovative approach which is increasingly seen as a source of competitive advantage.This study attempts to investigate the use of established and proven AI tools and techniques in supporting end-users of knowledge management systems through more efficient elicitation and representation of corporate knowledge.Case studies are used to show the situations of knowledge management systems in the construction organisations.From the results of the case studies, this paper attempts to show the usefulness of deploying AI tools and techniques in capturing and representation knowledge in the context of the construction industry.